A, The LEGAL ANALYSIS OF LEGITIME PORTIE FOR CHILDREN IN INSIDE AND OUTSIDE LEGITIMATE MARRIAGE IN CIVIL CODE (BURGERLIJK WETBOEK) - Nugraheni, Prasasti Dyah (DIKTUM: Jurnal Syariah dan Hukum, 2019)
The inheritance law in a Civil Code (Burgerlijk Wetboek) is one part of a civil law that has the basic nature of regulating something and there is no element of coercion in the inheritance law. Because this inheritance law is one part of a civil law that has the basic nature of regulating, then in this inheritance law there are rules governing an heir to his assets as long as an heir is still alive. To obtain an inheritance, it can be done in two ways, which include obtaining an inheritance based on the law and obtaining an inheritance based on a will (ad testamento). To obtain an inheritance based on the law, then there must be an absolute part (legitime portie) of an inheritance, namely the existence of an absolute part that is used to protect an inheritance from the actions of an heir who can make a will (ad testamento) which deviates from an absolute part (legitime portie). Keywords: Legitime portie, absolute part, heirs, children The inheritance law in a Civil Code (Burgerlijk Wetboek) is one part of a civil law that has the basic nature of regulating something and there is no element of coercion in the inheritance law. Because this inheritance law is one part of a civil law that has the basic nature of regulating, then in this inheritance law there are rules governing an heir to his assets as long as an heir is still alive. To obtain an inheritance, it can be done in two ways, which include obtaining an inheritance based on the law and obtaining an inheritance based on a will (ad testamento). To obtain an inheritance based on the law, then there must be an absolute part (legitime portie) of an inheritance, namely the existence of an absolute part that is used to protect an inheritance from the actions of an heir who can make a will (ad testamento) which deviates from an absolute part (legitime portie).